Book Review of Kassan and Moodley’s Diversity and Social Justice in Counseling, Psychology, and Psychotherapy: A Case Study Approach - Rine-Reesha, Naseem (Canadian Journal of Counselling and Psychotherapy, 2022)
An increasing focus on issues of diversity and social justice in counselling, psychology, and psychotherapy has been met with a range of responses and potential paths forward. In Diversity and Social Justice in Counseling, Psychology, and Psychotherapy: A Case Study Approach, editors Anusha Kassan and Roy Moodley assemble an exciting collection of new work from veterans and emerging scholars. This work challenges traditional conceptions of multicultural practice, broadens the range of conversations about diversity, and considers how issues of intersectionality affect the impact of different identities in practice. The incorporation of a case study into each chapter lends coherence to the array of styles and approaches represented in the collection and provides a practical application of theoretical considerations. Novice and experienced practitioners, instructors, and students will find both enjoyment and critical insights in this book.